Neural Network Modeling of Physicochemical Processes in Fluvisols with the Application of Sewage Sludge as Fertilizer for Energy Crops - Halyna Hrytsuliak; Miroslav Rimar; Vasyl Lopushniak; Andrew Kotsyubynsky; Teodoziia Yatsyshyn; Andrii Iatsyshyn; Jan Kizek; Peter Oravec; Vasyl-Danylo Liakh; Marcel Fedak (Agriculture)
This study investigates the impact of sewage sludge-based composts on the quality of sod-podzolic soils (Fluvisols, WRB), which are naturally acidic and low in fertility. A field experiment with eight variants was conducted, applying different doses of sewage sludge and composts mixed with organic materials to enhance soil properties. Energy crops, including Salix viminalis L., Miscanthus × giganteus, and Panicum virgatum L., along with Helianthus tuberosus, were cultivated in three replications to ensure research reliability. The study assessed changes in physicochemical soil properties, nutrient availability, and heavy metal accumulation within the soil-plant-ash continuum. Results indicated that compost application improved soil fertility, increased biomass yields, and influenced heavy metal dynamics, with variations depending on the applied compost type and dosage. The findings highlight the potential of sewage sludge composts to enhance soil productivity while maintaining environmental safety.